Operating in the digital economy: m-commerce adoption in Chinese family business - Zhang, Meng (2019)
This study aims to investigate the relationship between all three dimensions of perceived strategic value of m-commerce (operational support, managerial productivity and strategic decision aids), antecedents of m-commerce (organisational readiness, external context and m-commerce competence) and m-commerce adoption. The present study will further examine a mediation model in which all three dimensions of perceived strategic value of m-commerce affect m-commerce adoption through IT investment.